Development of a “Clear-Heat-and-Detoxify” Chicken Breast Prepared Dish Using Molecular Gastronomy - Wang Xinping (BIO Web of Conferences)
In this study, we combined the traditional Chinese medicinal formula “Wu Wei Xiao Du Yin” (Five-Ingredient Detoxification Decoction) with a low-temperature vacuum cooking approach from molecular gastronomy to develop a functional prepared chicken breast product with both “clear-heat-and-detoxify” efficacy and high-protein characteristics. The formula leverages the synergistic action of herbs such as Lonicera japonica (Jinyinhua), Forsythia suspensa (Lianqiao), Houttuynia cordata (Yuxingcao), Taraxacum mongolicum (Pugongying), and Chrysanthemum indicum (Yejuhua). The low-temperature vacuum cooking approach preserves heat-sensitive compounds in herbs by precisely controlling temperature and maintaining a vacuum environment. Thereby avoiding the degradation caused by high temperatures. This technique reduces the oxidation reaction of herbs and protecting oxidation-prone active ingredients. Additionally, prolonged low-temperature cooking ensures the gradual release of active compounds from the herbs. A series of experiments optimized temperature and cooking time, aiming to preserve nutrients, maintain herbal potency, and improve meat texture. Experimental analyses confirm that this product meets modern health-oriented and convenient consumption needs while helping to prevent common inflammatory diseases. This work underlines the value of integrating Traditional Chinese Medicine (TCM) theories with contemporary food processing techniques and has significant implications for expanding the repertoire of functional prepared foods and promoting “food as medicine” concepts.